Selection of a phase change material for energy storage by multi-criteria decision method regarding the thermal comfort in a vehicle. (July 2022) - Nicolalde, Juan Francisco; Cabrera, Mario; Martínez-Gómez, Javier; Salazar, Rodger Benjamin; Reyes, Evelyn
Abstract: The use of vehicles is a daily matter worldwide, however, they remain parked most of the time and commonly under the heating sun, leading to a rise in the internal temperature that provokes heating discomfort, and when the temperature drops this discomfort to the user is felt as cold. In this way, to reduce the distress drivers use air-conditioners in the first case and heaters in the second event as needed, making the consumption of energy a common activity. This research method takes a list of phase change materials used in some applications and makes a novel selection of the best material to be implemented on a vehicle's rooftop, which is done by Multicriteria Decision Methods means. The weighting is done by the Entropy weighting method compared with the new method based on the removal effect of criteria (MEREC), the decision-making methods VIKOR, COPRAS and TOPSIS choose the best material and the Spearman's correlation verify its agreement. The best material selected unanimously is the savENRG PCM-HS22P, which latter was simulated by finite elements methods, resulting in the reduction of 9 °C in the internal air when heating and conservation of 4 °C in the cooling with an increasing Phase Change Material layer. Highlights: Selection of an energy storage material by the utilization of Multicriteria Decision Methods Criteria weight determination of phase change materials by the method based on removal effect of criteria (MEREC) Application of Phase Change materials for internal air thermal comfort in automotive Computational simulation of the thermal charging and discharging events that occur in a parked vehicle situation. Energy storage of heat for energetic efficiency on transportation vehicle